Body weight gain and risk of colorectal cancer: a systematic review and meta‐analysis of observational studies. Issue 7 (29th April 2015) - Schlesinger, S.; Lieb, W.; Koch, M.; Fedirko, V.; Dahm, C. C.; Pischon, T.; Nöthlings, U.; Boeing, H.; Aleksandrova, K.
Summary While the relationship between body mass index as an indicator of excess body weight and the risk of colorectal cancer (CRC) is well established, the association between body weight gain in adulthood and risk of CRC remains unresolved. We quantified this association in a meta‐analysis of 12 observational studies published until November 2014 with a total of 16, 151 incident CRC cases. Random effect models were used to obtain summary relative risks (RR) and 95% confidence intervals (95% CIs). Between‐study heterogeneity was assessed using I2 statistics. Overall, the summary RR (95% CI) was 1.22 (1.14–1.30) for high body weight gain (midpoint: 15.2 kg) compared with stable weight (P for heterogeneity = 0.182; I2 = 21.2%). In a dose‐response analysis, each 5 kg weight gain was associated with a 4% (95% CI: 2%–5%) higher risk of CRC. The association persisted after adjustment for body weight at younger age and was present for both men and women, as well as for colon and rectal cancer. Differences by sex were detected for colon cancer (P for interaction = 0.003, with higher risk for men than women), but not for rectal cancer (P for interaction = 0.613). In conclusion, these data underscore the importance of body weight management from early adulthood onwards for the prevention of CRC development.